"Pitch-Class set Usage and development in late-Period improvisations of John Coltrane". (2nd January 2020) - O'Gallagher, John
ABSTRACT: The recordings Stellar Regions and Interstellar Space, made by John Coltrane shortly before his death in 1967, are among his least studied and understood works. While these recordings are generally regarded as representative of "free jazz, " three case studies present evidence that Coltrane's improvisations on these recordings are highly organized, utilizing a structural methodology focused on trichordal pitch-class sets. Musical set theory is used as a primary analytical tool in combination with common jazz harmonic and improvisational practices. Analyses will illustrate the extensive use of Tn -types (0, 1, 3) in "Iris, " and (0, 2, 4), and (0, 2, 5) in "Saturn." As an exemplar of this methodology, compelling evidence in "Iris" demonstrates the use of Tn -type (0, 1, 3), as a structural progenitor for both the saxophone improvisation and piano accompaniment for the entire length of the piece. En route, the potential influence of Nicolas Slonimsky's Thesaurus of Scales and Melodic Patterns (1947) is examined. As an archetype for an improvisational methodology focused on pitch-class sets, the significance of "Iris" resonates throughout Stellar Regions and Interstellar Space and more broadly to Coltrane's other late-period recordings, challenging the persistent characterization of this music as chaotic and "free."